2018
DOI: 10.1177/1756287218754766
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of psychosocial stress factors in patients with renal cancer

Abstract: There is a significant number of patients with renal cancer with increased psychological distress and a consecutive need for psychosocial care. This is underreported and largely unrecognized by patients as well as physicians and nurses. Easy-to-use assessment tools can be very helpful in identifying patients in need and this information can be used to implement psychological support and thus improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…German study on bladder cancer revealed a signi cantly higher distress level and expressed need for psychosocial support in patients with progressive disease compared to those at rst diagnosis [20].…”
Section: Discussionmentioning
confidence: 97%
“…German study on bladder cancer revealed a signi cantly higher distress level and expressed need for psychosocial support in patients with progressive disease compared to those at rst diagnosis [20].…”
Section: Discussionmentioning
confidence: 97%
“…Bladder cancer patients were also found to have an increased risk of suicide compared to prostate and kidney cancer [ 20 ]. In addition, a recent study showed that for kidney cancer, there is a significant number of patients with increased psychological distress and a consecutive need for psychosocial care [ 21 ]. A similar finding has been shown for patients with testicular or penile cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can subsequently cause psychological stress stemming not only from concern about survival, but also from uncertainty and changes in identity. In a recent study, 27% of patients undergoing treatment for kidney cancer were found to require psychosocial care [3]. Even patients with early-stage kidney cancer described anxiety, pain, sadness, and difficulty in sleeping [3].…”
Section: Harms Of Overdiagnosismentioning
confidence: 99%
“…In a recent study, 27% of patients undergoing treatment for kidney cancer were found to require psychosocial care [3]. Even patients with early-stage kidney cancer described anxiety, pain, sadness, and difficulty in sleeping [3]. Furthermore, a cancer diagnosis often leads patients to seek additional medical care, may adversely alter patients' financial and social planning, and can increase the odds of suicide [3].…”
Section: Harms Of Overdiagnosismentioning
confidence: 99%
See 1 more Smart Citation